Characterization and evaluation of creepy waves in Zigbee body area networks - Habaebi, Mohamed Hadi; Abdi, Mohamed Jama; Zyoud, Al-Hareth; Ahmed, Musse Mohamud (2014)
With the regard to the advancement in technology, Body Area Network (BAN) is one of the increasing interests for a number of applications, such as medical-sensor networks. Designing and evaluating its characteristics is necessary as they are used to monitor vital signs of human body which has to be accurate, reliable and secure. This paper reviews the main characteristics of on body communication network using Zigbee Body Area Network. Measurements of signal strength and the creepy waves of transmitted and received signals are performed. The measurements are conducted in a room environmental by performing those measurements on human body in different scenarios. Those measurements could be useful to propose a power saving scheme which reduce the power consumption and increase the sensor battery life.